Teaching and learning in integrated social studies: What knowledge is most important for students to acquire? - Olovsson, Tord Goran (JSSE - Journal of Social Science Education, 2022)
Teaching shows patterns of different discourses of learning in varying degrees of integration When grading is introduced, the subject knowledge discourse turns more dominant. Students show greater engagement in higher degrees of integrated teaching directed by overarching curriculum objectives. Macro policies direct the characteristics of the teaching, but there are variations in the strength with which different policies are implemented. Purpose: The purpose is to analyse how teaching and learning take place in integrated social studies teaching in relation to various curriculum goals and what consequences the teaching has for students’ approaches to learning. Design/methodology/approach:Ethnographic fieldwork is used in ten integrated thematic units conducted in four classes in four Swedish schools, with students in Years 5 and 6. Findings: The grading in Year 6 contributes to the integrated teaching being more adapted and directed towards subject knowledge goals. Students are very committed and involved in higher degrees of integration and discourses of learning connected to overarching curriculum objectives and are more focused and performance-oriented when the subject knowledge discourse creates a dominant pattern. Practical implications: Teaching in social studies should consist of the whole range of learning discourses, and how different knowledge conceptions can affect teaching and students’ learning should also be considered